In Vivo Evaluation of a Novel Radiofrequency Ablation Electrode in Pig Livers - Sung-Hyun Cho; Dongwook Oh; Gunn Huh; Tae-Jun Song; Dong-Wan Seo (Applied Sciences, 2022)
(1) Background: Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) is an alternative treatment for pancreatic tumors. Currently, EUS-RFA has been trialled to treat hepatic tumors. However, little has been reported about optimal settings for EUS-RFA in patients with hepatic tumors. We evaluated the ablation effect after in vivo RFA using a new EUS-RFA electrode in a pig model. (2) Methods Four pigs were used for the in vivo test. The in vivo testing was divided into two tests based on the length of the RFA electrode (0.5, 0.7, 1 or 1.5 cm), the ablation power (30 W or 50 W), and the ablation time (10 or 15 s). In test one, ablation effect was evaluated based on the electrode length and power. In test two, ablation effect was assessed based on power and time. (3) Results: In test one, the ablation width and depth correlated with the length of the electrode and power (0.5 cm, 10 W, 10 s: width 0.46 cm, depth 0.65 cm vs. 1.5 cm, 75 W, 10 s: width 0.77 cm, depth 1.80 cm). In test two, ablation width and depth were similar when RFA was set at 1.5cm, 50 W, and 10 s or 1 cm, 30 W, and 15 s (0.65 cm, 1.14 cm vs. 0.65cm, 1.26 cm). (4) Conclusions: The relationship between electrode length, ablation power, and ablation time, and the resulting ablation effect in pig livers suggest that EUS-RFA produces effective ablation while minimizing thermal injury.